2015
DOI: 10.1103/physrevb.92.245432
|View full text |Cite
|
Sign up to set email alerts
|

Cavity quantum electrodynamics with mesoscopic topological superconductors

Abstract: We study one-dimensional p-wave superconductors capacitively coupled to a microwave stripline cavity. By probing the light exiting from the cavity, one can reveal the electronic susceptibility of the p-wave superconductor. We analyze two superconducting systems: the prototypical Kitaev chain, and a topological semiconducting wire. For both systems, we show that the photonic measurements, via the electronic susceptibility, allows us to determine the topological phase transition point, the emergence of the Major… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 50 publications
0
61
0
Order By: Relevance
“…The latter method is particularly interesting as it allows to access also the exited states of the junction. There are several theoretical works that study the interplay of the Majorana fermions physics and microwaves in a superconducting cavity QED setup [24][25][26][27][28][29][30][31][32][33][34] . In contrast to the usual electronic methods, this approach is unique in that it can be totally non-invasive, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The latter method is particularly interesting as it allows to access also the exited states of the junction. There are several theoretical works that study the interplay of the Majorana fermions physics and microwaves in a superconducting cavity QED setup [24][25][26][27][28][29][30][31][32][33][34] . In contrast to the usual electronic methods, this approach is unique in that it can be totally non-invasive, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the quantum shot noise of the coherent conductor under the ac-bias can squeeze the photonic field [35]. Recent theoretical studies [14] indicate that in the limit when the charge susceptibility is small, i.e. |Π(ω)| ≪ κ, the ratio Π ′ (ω)/κ aproximates the phase shift and Π ′′ (ω)/κ corresponds to the cavity peak broadening, where the primed and double-primed quantities are the real and imaginary parts of the charge susceptibility.…”
Section: Microwave Probed Cavitymentioning
confidence: 99%
“…This is a well suited approximation for the tunneling junctions [22] or QDs [12,14] coupled to normal leads as long as the inter-level energy spacing of the electronic system δ l ≪ ω 0 , otherwise the decoupling of the photons from the QD is no longer possible, and the electronic transport is affected [18,19]. This condition is not satisfied in our setup, as the energy of the excited Shiba states inside the superconding gap, E S ∼ ω 0 , so decoupling the photons from the QD is not possible.…”
Section: A Model Hamiltonianmentioning
confidence: 99%
See 2 more Smart Citations